2024
DOI: 10.3389/fradi.2023.1326831
|View full text |Cite
|
Sign up to set email alerts
|

Empowering breast cancer diagnosis and radiology practice: advances in artificial intelligence for contrast-enhanced mammography

Ketki K. Kinkar,
Brandon K. K. Fields,
Mary W. Yamashita
et al.

Abstract: Artificial intelligence (AI) applications in breast imaging span a wide range of tasks including decision support, risk assessment, patient management, quality assessment, treatment response assessment and image enhancement. However, their integration into the clinical workflow has been slow due to the lack of a consensus on data quality, benchmarked robust implementation, and consensus-based guidelines to ensure standardization and generalization. Contrast-enhanced mammography (CEM) has improved sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The potential role of AI in the interpretation of contrast-enhanced mammography examinations was recently pointed out in a commentary by Zhang et al [95]. As mentioned in a 2024 review article by Kinkar et al [96], several studies demonstrated good performance from automatic segmentation and classification models for contrast-enhanced mammograms.…”
Section: Contrast-enhanced Mammographymentioning
confidence: 97%
“…The potential role of AI in the interpretation of contrast-enhanced mammography examinations was recently pointed out in a commentary by Zhang et al [95]. As mentioned in a 2024 review article by Kinkar et al [96], several studies demonstrated good performance from automatic segmentation and classification models for contrast-enhanced mammograms.…”
Section: Contrast-enhanced Mammographymentioning
confidence: 97%